Developing expertise and managing inaccessibility: a study of reading by listening practices among students with blindness or vision impairment - Anna Lundh (Information Research: An International Electronic Journal)
Introduction. This study aims to contribute to a better understanding of the learning that reading by listening requires from readers with print disabilities.